(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article examines the problem of digital addiction among teenagers and its impact on their physical, psychological, and social development. It analyzes the causes of excessive use of digital devices, including smartphones, social media, and online games. The paper also discusses the negative consequences such as reduced academic performance, weakened interpersonal communication skills, and mental health issues. In addition, possible solutions for preventing and reducing digital addiction are proposed.